Serum of patients with Guillain-Barre syndrome modulates mitogen-induced cytokine synthesis by normal peripheral blood mononuclear cells - Osna, Natalia; Logina, I.; Vilgert, N.; Hagina, E.; Bersinsh, Y.; Zvirbliene, A.; Shitova, O.; Kirschfink, Michael; Sochnev, A. (Central European journal of immunology, 1999)
Molecular mechanisms in the pathogenesis of the Guillain-Barre Syndrome (GBS) are still obscure. There is some evidence that cytokines (especially interferon gamma: IFN-γ and tumour necrosis factor: TNF-α) are implicated in the disease development. In this study we investigated the possible impact of sera of GBS patient on the synthesis of IFN-γ and TNF-α by normal mononuclear cells. Peripheral blood mononuclear cells of healthy donors were exposed to mitogens in the presence or absence of GBS patients sera, and cytokines were measured in the supernatants. Cytokine production was modulated in a stage-dependent manner: at the progression phase, GBS sera up- regulated; whereas at the recovery phase patient's sera down-regulated both IFN-γ and TNF-α production. IFN-γ down-regulation was partly associated with the increased production of IL-10. Analysis of the C3 split product C3d revealed a strong activation of the complement system in GBS sera, thereby providing further evidence for a possible triggering effect of the complement on cytokine production and disease progression.